Ethical choices and behavior of young people in the organization; influencing factors = Wybory etyczne i zachowania młodych w organizacji; czynniki je kształtujące - Stankiewicz, Janina; Łychmus, Patrycja (Zielona Góra: Faculty of Economics and Management Press)
The main focus of an article became the answers to questions: what factors control the behavior of people involved in business activities in a situation of choice between ethical and cost-effective action, and how important is ethics of individuals when they are making this kind of decision? From this perspective interesting are those who "have not yet entered the labor market", and therefore their individual ethics has not been subjected to the pressure of business practice in its ethical and unethical dimension. What are their opinions on business ethics? What values in business are important to them?
Keywords: działalność gospodarcza; działania ludzi; etyka; zachowania etyczne; etyka indywidualna; wybory etyczne; economic activity; people activities; ethics; ethical behavior; individual ethics; ethical choices